2013
DOI: 10.1063/1.4802686
|View full text |Cite
|
Sign up to set email alerts
|

Substrate strain manipulation by nanostructure perimeter forces

Abstract: Strain analysis in silicon substrates under uniaxial and biaxial stress by convergent beam electron diffractionStrain-induced self-organized growth of nanostructures: From step bunching to ordering in quantum dot superlattices J.Edge forces exerted by epitaxial nanostructures are shown to induce high levels of strain in the substrate. These very high localized forces appear at the perimeter and the resulting strain can be exploited to engineer the functional properties of the substrate. High levels of strain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In recent years, intensive investigations have been pursued to promote more efficient radiative recombination in Ge [1][2][3][4][5][6][7][8][9][10]. Most of them rely on early proposals of inducing an indirect-to-direct gap transition by tensile strain [11] or Sn alloying [12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, intensive investigations have been pursued to promote more efficient radiative recombination in Ge [1][2][3][4][5][6][7][8][9][10]. Most of them rely on early proposals of inducing an indirect-to-direct gap transition by tensile strain [11] or Sn alloying [12].…”
Section: Introductionmentioning
confidence: 99%
“…19 show that such material should be optimal for strain-transfer via nanopatterning, as has recently been demonstrated for SiGe on Si. 22,23 …”
Section: Parametermentioning
confidence: 99%
“…21 It has been shown that patterning of compressively strained SiGe alloys on Si(001) substrates leads to the transfer of compressive strain into the substrate. 22,23 An analogous process should therefore be feasible in which patterned tensile SiGe alloys on Ge(001) substrates induce tensile strain in the Ge. 19 Relaxation and metastability have been extensively studied in compressive SiGe alloys on Si(001).…”
mentioning
confidence: 99%
“…A direct-gap semiconductor which is fully compatible with Si-based technology would suggest the possibility of highly efficient Si-compatible emitters of infrared radiation, which would greatly facilitate full integration of electronics and optoelectronics [5][6][7]. We have already demonstrated that topdown SiGe structures, fabricated by nanolithography, can be used as stressors for the creation of strong deformation fields and high strain in bulk substrates [8,9]. However, finite-element simulations suggest that a stressor patterned on a free-standing Ge membrane allows for a larger highly strained active area with respect to strained bulk material [10,11].…”
Section: Introductionmentioning
confidence: 97%